2016
DOI: 10.1108/s1479-067x20160000015006
|View full text |Cite
|
Sign up to set email alerts
|

Effectuation Spectra in Chinese High-Tech Entrepreneurship: Domain-Specific Logic Orientations and Cross-Border M&A

Abstract: As the developing nations grow and experience rapid institutional transformation, research has begun to investigate the roles of culture, cognition and institutional context on entrepreneurship and innovation. This chapter aims to advance the entrepreneurial cognition literature by juxtaposing entrepreneurial effectuation, domain-specific expertise and ambiguity. By conducting a qualitative study of Chinese high-tech domestic and returnee entrepreneurs, the authors propose a spectrum between causation and effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 131 publications
(111 reference statements)
0
3
0
Order By: Relevance
“…The international cultural context may further complicate the entrepreneurial team cognition. One recent study based on returnee and domestic entrepreneurs in China found entrepreneur team's domain-specific expertise can influence their causation or effectuation logic (two distinctive logics of reasoning) in the pursuit of entrepreneurial opportunities (Liu & Isaak, 2016). Hence, when entrepreneurial team contains members who are bi-culturalism, it may enhance the cognitive complexity on the team-level.…”
Section: Entrepreneurial Team Cognition and Strategic Sensitivitymentioning
confidence: 99%
“…The international cultural context may further complicate the entrepreneurial team cognition. One recent study based on returnee and domestic entrepreneurs in China found entrepreneur team's domain-specific expertise can influence their causation or effectuation logic (two distinctive logics of reasoning) in the pursuit of entrepreneurial opportunities (Liu & Isaak, 2016). Hence, when entrepreneurial team contains members who are bi-culturalism, it may enhance the cognitive complexity on the team-level.…”
Section: Entrepreneurial Team Cognition and Strategic Sensitivitymentioning
confidence: 99%
“…However, there is still lack of research aimed at investigating the micro‐foundation of effectuation theory, especially in the context of international entrepreneurship (Felin, Foss, & Ployhart, ; Reymen et al, ). By comparing domestic and returnee entrepreneurs, one recent study uncovered the influence of culture on domain‐specific expertise, which, in turn, leads to effectual or causal approaches taken by entrepreneurs in dealing with perceived ambiguity (Liu & Isaak, ). The behavioural approaches adopted by entrepreneurs to interpret, enact, and respond to risk may offer nuanced understandings of effectuation theory, especially through the lens of resilience and coping strategies development.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…One recent study elaborates the potential benefits brought by bi-cultural individuals to the M&A domain by particular reference to domain-specific logic orientations (i.e. as opposed to knowledge-crossing boundaries) (Liu & Isaak, 2016). Furthermore, a recent review of talent management suggests that a deeper appreciation of organizational contextual factorswellexemplified by bi-cultural employees -may significantly assist the scholarly advancement of talent management research (Collings, Scullion, & Vaiman, 2015).…”
Section: Bi-cultural Employees In the Cross-cultural Manda Contextthe...mentioning
confidence: 99%